The ‘Double Movements’ of Neighbourhood Change: Gentrification and Public Policy in Harlem and Prenzlauer Berg - Bernt, Matthias (Urban Studies (Sage Publications, Ltd.), 2012)
This article explores the interrelation of gentrification and public policies in the neighbourhoods of Prenzlauer Berg (Berlin) and Harlem (New York City). It draws on Karl Polanyi’s concept of a ‘double movement’ and argues that gentrification is fundamentally a political process. Thus, while demise in the face of market forces, or even an active support of gentrification, is clearly visible in both neighbourhoods, the relation between public policies and gentrification is also highly unstable and contradictory. The cases studied highlight that the resources to push or prevent gentrification are contingent; they are not built into the essence of urban development.
Keywords: Berlin (Germany); Germany; Harlem (New York, N.Y.); economic conditions; gentrification; government policy; social conditions; urban planning; urban renewal

Neoliberalismo Crisis Actual - Peck, Jamie (Documentos y Aportes en Administración Pública y Gestión Estatal, 2012)
The article discuss the characteristic of the current neoliberalism to understand it as a changeable and complex project whose economic and political sustainability is continuously reinvented and whose governance and spatiality is in need of being understood differently, if a viable alternative is to be constructed. Taking the recent neoliberal crisis as a point of departure, it discusses three main and interrelated aspects: firstly, the polymorphic characteristics of neoliberalism as a process in transformation; secondly, the way in which it could be acted against this neoliberal process by bringing some contributions from Polanyi back into the analysis so as to understand neoliberalism's dynamics; thirdly, the characteristics of some current policies taking place under neoliberal process, some of which could became viable alternatives in the long term. (English)
Keywords: 21st century; POLANYI, Karl, 1886-1964; crisis; economic history; global financial crisis, 2008-2009; neoliberalism; neoliberalismo; political philosophy; political practices; practical politics; prácticas políticas; world politics - economic aspects

The point is to keep going: the global sub-prime mortgage crisis, local labour market repositioning, and the capital accumulation dynamic in Singapore - Lim, Kean Fan (Journal of Economic Geography, 2012)
The global subprime mortgage crisis in 2007–2008 led to an economic recession in Singapore, but the economy recovered strongly to post a 14.5% expansion in 2010. This article examines how labour market repositioning policies contributed to this recovery. Following Karl Polanyi's conceptualization of the economy as an ‘instituted process’, I explore how these policies function as state-driven redistributive strategies aimed at triggering reciprocal responses from employers and workers within the putatively self-regulatory local labour market. The Singapore case foregrounds the causal roles of place- and time-specific state–firm–labour interactions in precluding what Polanyi calls society's ‘double movement’ against market-driven regulation. This successful preclusion exemplifies how the conditions and relations of economic production are not reproduced solely through market exchange; to sustain the capital accumulation dynamic, complementary acts of reciprocity and redistribution from different socio-economic stakeholders could be equally, if not more, important.
Keywords: Singapore; capital accumulation dynamic; economic recovery; global financial crisis; instituted economy; labor market; local labour market; saving and investment; spatio-temporal variation; spatio–temporal fix